2023
DOI: 10.1002/anie.202301049
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of BaZrS3 and BaHfS3 Chalcogenide Perovskite Films Using Single‐Phase Molecular Precursors at Moderate Temperatures

Abstract: Chalcogenide perovskites have garnered interest for applications in semiconductor devices due to their excellent predicted optoelectronic properties and stability. However, high synthesis temperatures have historically made these materials incompatible with the creation of photovoltaic devices. Here, we demonstrate the solution processed synthesis of luminescent BaZrS3 and BaHfS3 chalcogenide perovskite films using single‐phase molecular precursors at sulfurization temperatures of 575 °C and sulfurization time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…40 This issue was circumvented in a more recent report by Agrawal in collaboration with the Bart group, in this case using true solution-phase molecular precursors for thin film fabrication. 46 In this report, a barium bis(dithiocarboxylate) complex and a zirconium tetrakis(dithiocarbamate) complex, both of which are generated in situ by insertion reactions of CS 2 into the appropriate precursor complex, are combined in pyridine solution, deposited by blade-coating, annealed, and sulfurized at 575 1C to produce BaZrS 3 (Fig. 8…”
Section: (G)-(i))mentioning
confidence: 99%
See 2 more Smart Citations
“…40 This issue was circumvented in a more recent report by Agrawal in collaboration with the Bart group, in this case using true solution-phase molecular precursors for thin film fabrication. 46 In this report, a barium bis(dithiocarboxylate) complex and a zirconium tetrakis(dithiocarbamate) complex, both of which are generated in situ by insertion reactions of CS 2 into the appropriate precursor complex, are combined in pyridine solution, deposited by blade-coating, annealed, and sulfurized at 575 1C to produce BaZrS 3 (Fig. 8…”
Section: (G)-(i))mentioning
confidence: 99%
“…However, Agrawal and Bart have reported the preparation of BaHfS 3 thin films from solution-phase molecular precursors, by an extension of the protocols described above for the preparation of BaZrS 3 thin films. 46…”
Section: (B))mentioning
confidence: 99%
See 1 more Smart Citation
“…To tackle the toxicity and stability issues of inorganic–organic lead-halide-based perovskites, chalcogenide perovskites have been viewed as an alternative material of semiconductors for optoelectronic and solar cell applications . Numerous investigations have reported various chalcogenide perovskites for excellent efficiency photovoltaic cells and photoelectrocatalytic water splitting. Among these inorganic chalcogenides based on perovskites, BaZrS 3 is a good contender for a solar cell absorber because it has an extraordinarily high near-edge absorption coefficient of more than 10 5 cm –1 . ,, Dependent upon manufacturing circumstances, this material also has a respectable room-temperature mobility, varying from 2.3 to 13.7 cm 2 V –1 s –1 . BaZrS 3 exhibits band gap values experimentally ranging between 1.74 and 1.94 eV. BaZrS 3 also exhibits higher structural stability and moisture stability .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have reported various chalcogenide perovskites for excellent efficiency photovoltaic cells and photoelectrocatalytic water splitting. Among these inorganic chalcogenides based on perovskites, BaZrS 3 is a good contender for a solar cell absorber because it has an extraordinarily high near-edge absorption coefficient of more than 10 5 cm –1 . ,, Dependent upon manufacturing circumstances, this material also has a respectable room-temperature mobility, varying from 2.3 to 13.7 cm 2 V –1 s –1 . BaZrS 3 exhibits band gap values experimentally ranging between 1.74 and 1.94 eV. BaZrS 3 also exhibits higher structural stability and moisture stability . It also showed that the optical absorption coefficient of BaZrS 3 is highly remarkable compared to all of the other useful solar cell absorbers, such as GaAs, CuInSe 2 , and MAPbI 3 .…”
Section: Introductionmentioning
confidence: 99%